Human‐Recombinant‐Elastin‐Based Bioinks for 3D Bioprinting of Vascularized Soft Tissues. Issue 45 (1st October 2020) - Lee, Sohyung; Sani, Ehsan Shirzaei; Spencer, Andrew R.; Guan, Yvonne; Weiss, Anthony S.; Annabi, Nasim
Abstract: Bioprinting has emerged as an advanced method for fabricating complex 3D tissues. Despite the tremendous potential of 3D bioprinting, there are several drawbacks of current bioinks and printing methodologies that limit the ability to print elastic and highly vascularized tissues. In particular, fabrication of complex biomimetic structure that are entirely based on 3D bioprinting is still challenging primarily due to the lack of suitable bioinks with high printability, biocompatibility, biomimicry, and proper mechanical properties. To address these shortcomings, in this work the use of recombinant human tropoelastin as a highly biocompatible and elastic bioink for 3D printing of complex soft tissues is demonstrated. As proof of the concept, vascularized cardiac constructs are bioprinted and their functions are assessed in vitro and in vivo. The printed constructs demonstrate endothelium barrier function and spontaneous beating of cardiac muscle cells, which are important functions of cardiac tissue in vivo. Furthermore, the printed construct elicits minimal inflammatory responses, and is shown to be efficiently biodegraded in vivo when implanted subcutaneously in rats. Taken together, these results demonstrate the potential of the elastic bioink for printing 3D functional cardiac tissues, which can eventually be used for cardiac tissue replacement. Abstract : New biocompatible and elastic bioinks based on recombinant human tropoelastin and gelatin for bioprinting of complex soft tissues is introduced. As proof of the concept, highly vascularized and functional 3D cardiac tissue constructs are bioprinted using a freeform reversible embedding of suspended hydrogels (FRESH) printing technique. The in vitro functionality and in vivo biocompatibility of the bioprinted structures are characterized.